Beyond the Original : Translation As Experiment - Marília Jöhnk (transcript, 2025)
Can DeepL and ChatGPT translate Shakespeare? The recent developments in AI present a timely opportunity to look at the concept of literary translation anew. The contributors to this volume delve into the playful and performative nature of translations that embrace ambiguity, confusion, and even failure. In doing so, they go beyond the conventional view of translation as a reproduction of the original. Highlighting translations that faced criticism or went unnoticed, the contributors offer a new perspective on well-known authors by looking at their lesser-known translated texts.